Correction: Solution-processable, niobium-doped titanium oxide nanorods for application in low-voltage, large-area electronic devices. Issue 10 (27th February 2018) - Alharthi, F. A.; Cheng, F.; Verrelli, E.; Kemp, N. T.; Lee, A. F.; Isaacs, M. A.; O'Neill, M.; Kelly, S. M.
Abstract : Correction for 'Solution-processable, niobium-doped titanium oxide nanorods for application in low-voltage, large-area electronic devices' by F. A. Alharthi et al., J. Mater. Chem. C, 2018, 6, 1038–1047.